Band structure and unconventional electronic topology of CoSi. (6th March 2018) - Pshenay-Severin, D A; Ivanov, Y V; Burkov, A A; Burkov, A T
Abstract: Semimetals with certain crystal symmetries may possess unusual electronic structure topology, distinct from that of the conventional Weyl and Dirac semimetals. Characteristic property of these materials is the existence of band-touching points with multiple (higher than two-fold) degeneracy and nonzero Chern number. CoSi is a representative of this group of materials exhibiting the so-called 'new fermions'. We report on an ab initio calculation of the electronic structure of CoSi using density functional methods, taking into account the spin–orbit interactions. The linearized k ⋅ p Hamiltonian, describing the anisotropic electronic structure of CoSi near the Γ point is derived. The topological features of band-touching nodes with four- and six-fold degeneracy located at the Γ and R points in the first Brillouin zone are analysed using the linearized Hamiltonians and first principle calculations. In particular, we show, using the non-Abelian Berry curvature, that these band-touching points carry topological charges of ± 4, which change signs at certain values of parameters of the Hamiltonians. We describe the resulting Fermi arc surface states and their spin texture. We also discuss the influence of many body G 0 W 0 corrections on the electronic band structure and the topological properties of CoSi.